Translating pharmacology models effectively to predict therapeutic benefit. Issue 6 (June 2022) - Dudal, Sherri; Bissantz, Caterina; Caruso, Antonello; David-Pierson, Pascale; Driessen, Wouter; Koller, Erich; Krippendorff, Ben-Fillippo; Lechmann, Martin; Olivares-Morales, Andrés; Paehler, Axel; Rynn, Caroline; Türck, Dietrich; et al.
Abstract : Many in vitro and in vivo models are used in pharmacological research to evaluate the role of targeted proteins in a disease. Understanding the translational relevance and limitation of these models for analyzing a drug's disposition, pharmacokinetic/pharmacodynamic (PK/PD) profile, mechanism, and efficacy, is essential when selecting the most appropriate model of the disease of interest and predicting clinically efficacious doses of the investigational drug. Selected animal models used in ophthalmology, infectious diseases, oncology, autoimmune diseases, and neuroscience are reviewed here. Each area has specific challenges around translatability and determination of an efficacious dose: new patient-specific dosing methods may help overcome these limitations.